Night shift work before and during pregnancy in relation to depression and anxiety in adolescent and young adult offspring - Strohmaier, Susanne (Eur J Epidemiol, 2019)
We investigated the relationship between maternal history of nightshift work before and shift work during pregnancy and offspring risk of depression and anxiety, among mothers participating in the Nurses Health Study II and in their offspring enrolled in the Growing Up Today Study 2 between 2004 and 2013. Case definitions were based on offspring self-reports of physician/clinician-diagnosed depression and/or anxiety, regular antidepressant use and depressive symptoms assessed using the Center for Epidemiologic Studies Depression Scale. Multivariable-adjusted odds ratios (ORs) and 95% confidence intervals (CIs) were estimated using generalized estimating equation models. We found no associations between maternal nightshift work before pregnancy or during pregnancy and offspring mental health disorders (e.g., nightshift work before pregnancy: depression (based on physician/clinician diagnosis): OR(ever nightwork )= 1.14; 95% CI, 0.88–1.47; either depression or anxiety: OR(ever nightwork )= 0.93; 95% CI, 0.81–1.08; nightshift work during pregnancy: depression: OR(ever nightwork )= 1.14; 95% CI, 0.68–1.94; depression or anxiety: OR(ever nightwork )=1.17; 95% CI, 0.70–1.98) and no dose-response relationship with longer history of nightshift work (all P(Trend  )>0.10). Stratifying by maternal chronotype revealed a higher risk of depression for offspring whose mothers worked nightshifts before pregnancy and reported being definite morning chronotypes (a proxy for circadian strain) (OR(ever nightwork )= 1.95; 95% CI, 1.17, 3.24 vs. OR(ever nightwork )= 0.93; 95% CI, 0.68, 1.28 for any other chronotype; P(Interaction )= 0.03). Further studies replicating our findings and refined understanding regarding the interplay of nightshift work and chronotype and its potential influences on offspring mental health are needed. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s10654-019-00525-2) contains supplementary material, which is available to authorized users.